Faktor-Faktor Yang Mempengaruhi Kebijakan Dividen Perusahaan Manufaktur Di BEI Saat Covid-19 - Monica Liliani; Anita Permatasari; Jeanne Asteria Wawolangi (Universitas Katolik Darma Cendika, 2023)
At the time of the Covid-19 pandemic, there have been restrictions on economic activity nationwide. The restrictions also have an impact on business activities and will have an impact on the slowing economy of world economic growth, including Indonesia. When the LSSR (Large-Scale Social Restrictions) took place in several major cities in Indonesia, many companies from various sectors went bankruptcy. One of them is the manufacturing sector. Dividends can be the main attraction for investors (Kristian and Viriany, 2021). Dividend policy can also be influenced by several factors such as liquidity, leverage, and company size. The object of research used in this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) in the 2020-2021 period. The research approach used is a quantitative approach. The data used in this study is secondary data. The sampling method used in this study was purposive sampling. The sample studied was 20 manufacturing companies. The results of this study are the first to state that the current ratio has an influence on dividend policy in the manufacturing industry during the Covid-19 pandemic for the 2020-2021 period. The second result states that the debt to equity ratio has no influence on dividend policy in the manufacturing industry during the Covid-19 pandemic for the 2020-2021 period. The third result stated that the size of the company has no influence on dividend policy in the manufacturing industry during the Covid-19 pandemic for the 2020-2021 period.